Have the iceberg B15 affected the POPs bioaccumulation in the Ross Sea? The case of Trematomus bernacchii - CORSOLINI, SIMONETTA; Cincinelli, A.; Martellini, T.; BARONI, DAVIDE; Randazzo, D. (2016)
The T. bernacchii is a Antarctic fish with a widespread distribution and high abundance in near-shore seawaters; thus it is considered a good bio-indicator for contamination study, assessment of changes in Antarctic ecosystem quality (1), and temporal trend evaluation. In this study, levels of various POPs were evaluated in Trematomus bernacchii. POP concentrations determined in different years (data from the literature) were analyzed in order to investigate their concentration trends and the possible influence of iceberg melting.